Glycosides from Medicinal Plants as Potential Anticancer Agents: Emerging Trends Towards Future Drugs - Khan, Haroon; Saeedi, Mina; Nabavi, Seyed Mohammad; Mubarak, Mohammad S; Bishayee, Anupam (Current medicinal chemistry, 2019)
Cancer continues to be a global burden, despite the advancement of various technological and pharmaceutical improvements over the past two decades. Methods for treating cancer include surgery, radiotherapy and chemotherapy in addition to other specialized techniques. On the other hand, medicinal plants have been traditionally employed either as the complementary medicine or dietary agents in the treatment and management of cancer. Medicinal plants are a rich source of secondary metabolites with interesting biological and pharmacological activities. Among these metabolites, glycosides are naturally occurring substances and have outstanding therapeutic potential and clinical utility. Different medical research engines such as, GoogleScholar, PubMed, SpringerLink, ScienceDirect were used to collect related literature on the subject matter. In this regard, only peer-reviewed journals were considered. Emerging results showed that numerous glycosides isolated from various plants possessed marked anticancer activity against a variety of cancer cell lines. Accordingly, the aim of the present review is to shed light on the anticancer effects of glycosides, analyze possible mechanisms of action, and highlight the role of these natural agents as complementary and alternative medicine in combating and managing cancer. The glycosides isolated from different plants demonstrated potent cytotoxic effects against various cancer cell lines in initial preclinical studies. The anticancer effect was mediated through multiple mechanisms; however further detailed studies are needed to understand the full potential of glycosides for clinical utility.